On the motive of the Incarnation - Juan, de la Anunciación, 1633-1701 (Early modern Catholic sources, 2019)
The Catholic University of America Press is pleased to announce a new series, Early Modern Catholic Sources, edited by Ulrich L. Lehner and Trent Pomplun. This series – the only one of its kind – will provide translations of early modern Catholic texts of theological interest written between 1450 and 1800. The first volume in this series is On the Motive of the Incarnation, the first English translation of the seventeenth-century Discalced Carmelites at the University of Salmanca treatise on the motive of the Incarnation. Originally intended for students of their order, it became a major contribution to broader theological discourse. In this treatise, they defend the assertion that God intended Christ’s Incarnation essentially as a remedy for sin, such that if Adam had not sinned Christ would not have become incarnate, and that, at the same time, God intended all other works of nature and grace for the sake of Christ at their end. The Salmanticenses’ position thus combines elements of the Franciscan and Dominican traditions, stemming from the thought of Blessed John Duns Scotus and Saint Thomas Aquinas. This treatise is an exhaustive effort to show how the Scotistic emphasis on the primacy of Christ as the first willed and intended by God can be articulated within a Thomistic framework that acknowledges the contingency of the Incarnation on the need for redemption. In addition to the translation, the volume will include a brief introduction and extensive notes for theologians, historians, and students.